A Survey on Generalized Topological Indices for Silicon Carbide Structure - Sajid Mahboob Alam; Fahd Jarad; Abid Mahboob; Imran Siddique; Taner Altunok; Muhammad Waheed Rasheed (Journal of Chemistry)
The application of graphs in chemical and molecular structures has exponentially increased during the last few years. Topological indices facilitate the collection of beneficial information and provide an approach to understanding the properties of chemical structure by providing information about algebraic graphs. Let G be a graph with u-vertices and Ωu be the degree of uth vertex. In this manuscript, we compute Zagreb index (ZI), first, and second, Hyper F-indices and sum and product connectivity of F-index of silicon carbides, namely, SiC4 – I[r, s] and SiC4 – II[r, s].